Management accounting information system in gas station business - SEPTRIADI, DICKY; ZARKASYI, WAHYUDIN; MULYANI, SRI; SUKMADILAGA, CITRA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this paper is to measure how effective the utilization of management accounting information system on the gas business station and its impact on the quality of information and optimization for decision-making. Effectiveness measured in the context of policies, people, processes and systems. This research was conducted in 235 gas stations located in the Western part of Java involving 235 respondents using questionnaire instruments and in-depth interviews with a key person. The results of the research revealed that the utilization of management accounting information systems has a positive impact on the quality of information.